Progressive multifocal leukoencephalopathy in two natalizumab-treated stepsisters: An intriguing coincidence. (February 2017) - Bacchetta, Frédéric; Mathias, Amandine; Schluep, Myriam; Du Pasquier, Renaud
Background: Natalizumab, a treatment used in multiple sclerosis (MS), is associated with cases of progressive multifocal leukoencephalopathy (PML). Objective: We describe two cases of PML in related but not genetically apparented natalizumab-treated MS patients who are stepsisters. Reported cases/outcomes: While Patient 1 developed PML, Patient 2 was on natalizumab and had contacts with Patient 1. Patient 2 was diagnosed with PML 5 months after Patient 1. Conclusion: The clinical and temporal data highly suggest that there was JC virus (JCV) transmission from one patient to the other with development of PML as primo-infection in Patient 2.